Palindromic rheumatism - an unusual Presentation of rheumatoid arthritis - Biswas, Sarmistha; Rahman, Anonnya; Das, Partha Pratim; Karim, Md Enamul; Khan, Abed Hussain; Afrose, Rafia; Dey, Pritam (Journal of Dhaka Medical College, 2013)
We have reported a 24 years old woman presenting with recurrent episodes of joint pain, weakness and fever for last one and half year. Each episode persists for 3/4 days and intervals between episodes are variable. Laboratory investigations showed positive RF and anti-CCP. Each episode remits spontaneously with some NSAIDs. The case high lights the need of accepting Palindromic presentation of early Rheumatoid arthritis and it is not very rare as we think. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15707 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 93-95